The comparison of dosimetric properties between gafchromic ebt-2 film and rtqa film in high energy photon beam and high energy electron beam - Leong, Nor Fathin Halina Nazlie (Universiti Sains Malaysia, 2016)
The aim of this work was to compare the dosimetric properties between Gafcromic EBT- 2 Film and Gafchromic RTQA Film in high energy photon beam and high energy electron beam. For calibration purpose, both films were cut into 3 cm x 3 cm and irradiated from 0 cGy to 600 cGy in 6 MeV, 9 MeV electron beam and 6 MV, 10 MV photon beam. For measuring percentage depth dose and beam profile, another RTQA film and EBT-2 film was irradiated with 400 MU. Then, all the film was scan by using Gafchromic Film Scanner (Flatbed Scanner EPSON EXPRESSION 10000 XL) after 24 hr irradiated. The result was analyzed by using Verisoft Software 5.1. The result shown EBT-2 film is more sensitive up to 6 Gy compare to RTQA film. The result of percentage depth dose for both films were compare to the result of ionization chamber and treatment planning system. The EBT-2 film shown in a good agreement with ionization chamber and treatment planning system compare to RTQA film. All the results of beam profile for RTQA film seen in a good agreement with EBT-2 film in terms of beam flatness and penumbra size. As a conclusion, the EBT-2 film is more suitable to be used in measured PDD and beam profile in high energy electron and photon beam.